Aortic valve surgery in the UK, trends in activity and outcomes from a 15-year complete national series. (21st May 2021) - Baghai, Max; Wendler, Olaf; Grant, Stuart W; Goodwin, Andrew T; Trivedi, Uday; Kendall, Simon; Jenkins, David P
Abstract:  : OBJECTIVES: Since the turn of the century, cardiac surgery has evolved quite notably. This study sought to investigate the trends in aortic valve surgery activity and subsequent outcomes in the UK by using a mandatory national cardiac surgical clinical database within the context of a comprehensive public healthcare system (National Health Service). METHODS: The UK National Adult Cardiac Surgery Audit database provided data for aortic valve surgery procedures performed between 2002 and 2016, and the data were validated and cleaned using reproducible algorithms. The findings and trends in in activity and outcomes were then analysed by financial year. RESULTS: During the study period, a total of 148 862 procedures were performed, with the number of cases per year peaking in 2014/2015 at 12 483. The mean in-hospital mortality rate for all aortic valve surgery has fallen from 5.6% to 3.4%, despite an increase in patient age and mean logistic EuroSCORE. While the number of isolated aortic valve replacements has remained stable at around 5000 per year, aortic valve replacement and coronary artery bypass graft have increased to over 3200 with transcatheter aortic valve implantation activity continuing to increase. CONCLUSIONS: This study demonstrates that despite an increase in patient risk profile, there has been a consistent reduction in in-hospital mortality within all aortic valve surgery procedures performed in the UK over a 15-year period. Increasing catheter-based interventions have not yet resulted in a significant decrease in surgical aortic valve replacements in the UK. Abstract : Aortic valve disease, in particular aortic stenosis (AS), is constantly rising owing to demographic changes.